Energy, Nitrogen and Mineral Exchange in the Body of Broiler Chicks (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Broiler mineral in nutrition and local probiotic from bacteria use metabolic energy indicators positive effect shows. Food of nitrogen metabolism and assimilation to do indicators different different eating of factors to the metabolism of the body as a whole effect determined.